1982
DOI: 10.1038/clpt.1982.176
|View full text |Cite
|
Sign up to set email alerts
|

Diphenhydramine: Kinetics and psychomotor effects in elderly women

Abstract: Kinetics and sedative and psychomotor effects of diphenhydramine were investigated in elderly Caucasian women (greater than 64 yr. old). In a double-blind trial, each of 12 healthy subjects received on one of three occasions 50 mg/70 kg IV or oral diphenhydramine HCl or oral placebo. Plasma levels of diphenhydramine were measured in six subjects and tests of sedation and psychomotor performance were performed hourly for 8 hr in all subjects. Kinetic analysis showed that the volume of distribution (295 +/- 50 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…Furthermore, there is no reason to suppose that the elderly would respond differently than the young on subjective ratings, which are not performance-based and are often the most sensitive indices of sedation (Lines et al, 1992). There is therefore little reason to doubt the validity of these findings, which support the data previously reported by Berlinger et al (1982) in elderly females.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, there is no reason to suppose that the elderly would respond differently than the young on subjective ratings, which are not performance-based and are often the most sensitive indices of sedation (Lines et al, 1992). There is therefore little reason to doubt the validity of these findings, which support the data previously reported by Berlinger et al (1982) in elderly females.…”
Section: Discussionsupporting
confidence: 59%
“…In a double-blind study, Berlinger et al (1982) reported that single oral and i.v. doses of diphenhydramine (50 mg/70 kg) had no effects on psychomotor tests and subjective ratings in elderly females (65-81 years).…”
Section: Introductionmentioning
confidence: 99%
“…In a comparison of healthy young and elderly subjects, diphenhydramine was metabolized at a similar rate and equally effective in reducing performance in memory and attention tasks. The elderly subjects, however did not report significant sedation [95]. Similarly, a lack of drowsiness was accompanied by statistically significant driving impairment [96] and performance on sorting tasks [95] after diphenhydramine.…”
Section: Clinical Studies: Daytime Effectsmentioning
confidence: 99%
“…Remarkably little is known about the risk profile of those who might be predisposed to sedation. Male gender [14] and older age [38] have been suggested as predictors of decreased susceptibility to antihistamine sedation. Race, weight, and disease status have seldom been examined.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%